2015
DOI: 10.1007/3418_2015_117
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed C–H Bond Functionalization Utilizing an N,N′-Bidentate Directing Group

Abstract: This review discusses the use of nickel catalysts and N,N 0 -bidentate directing groups, such as 2-pyridinylmethylamine, 8-aminoquinoline, and derivatives thereof, which constitute a powerful combination for the chelation-assisted functionalization of C-H bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 66 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…The latter was indeed characterized by typical signals for its IMes and Cp groups, but which are shifted compared to those of 3, as well as by two apparent triplets centered at 7.11 and 6.97 ppm, which integrate for one proton each relative to the Cp and IMes signals and correspond to the H(5) and H(6) protons of a benzothiazolyl unit. However, the signals of the H(4) and H (7) overlapped with those of unreacted benzothiazole and were not unambiguously observed. Complex 7 was also observed in the attempted couplings with the cationic complex 6 ( Figure S3), highlighting a general behaviour for these CpNi(NHC) species thereof.…”
Section: Catalytic Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…The latter was indeed characterized by typical signals for its IMes and Cp groups, but which are shifted compared to those of 3, as well as by two apparent triplets centered at 7.11 and 6.97 ppm, which integrate for one proton each relative to the Cp and IMes signals and correspond to the H(5) and H(6) protons of a benzothiazolyl unit. However, the signals of the H(4) and H (7) overlapped with those of unreacted benzothiazole and were not unambiguously observed. Complex 7 was also observed in the attempted couplings with the cationic complex 6 ( Figure S3), highlighting a general behaviour for these CpNi(NHC) species thereof.…”
Section: Catalytic Studiesmentioning
confidence: 89%
“…They instead form a C(2)-metallated benzothiazolyl complex that constitutes a potential energy well that quenches all further reactivity. Although benzothiazolyl complexes are often proposed as possible intermediates in such biaryl couplings, the isolated complex, [NiCp(C 7 H 4 NS)(IMes)] (7), is to our knowledge a very rare example of fully characterized C(2)-benzothiazolyl-nickel complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murai followed up this report in 1995 with a cross-coupling similar to his previous report, but utilizing organozinc reagents instead of alkynyl stannanes. 198 This multicomponent reaction featured an expanded substrate scope in regards to the terminal alkyne and the dialkyl organozinc reagent. Additional silyl groups could be introduced both on alkyne or zinc reagent.…”
Section: Multicomponent Couplings Of Silyl Electrophiles-murai Was Alsomentioning
confidence: 99%
“…Bower found that the substituent on the carbamate (R 1 in Figure 49) could be varied with the 5-exo substrates (e.g. [198][199][200]. However, for the 6-exo and 7-exo substrates (201)(202)(203) only the tert-butyl substituent on the carbamate provided the optimal yields.…”
Section: Aza-heckmentioning
confidence: 99%